2004
DOI: 10.1177/153537020422900915
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory Cytokine Genes are Constitutively Overexpressed in the Heart in Experimental Systemic Lupus Erythematosus: A Brief Communication

Abstract: The heart is one of a number of organs that may be affected in systemic lupus erythematosus (SLE), a prototypic autoimmune disease. Potential anatomical sites of involvement include the myocardium, pericardium, endocardium, valves, conduction system and blood vessels that subserve the heart. Typically, the severity of cardiovascular disease in lupus correlates with the degree of systemic inflammation, which is mirrored by the level of C-reactive protein (CRP) in the plasma. C-reactive protein, in turn is regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 39 publications
1
12
1
Order By: Relevance
“…IL-1b, IL-6 and TNF-a, pro-inflammatory cytokines, were central mediators for the regulation of several biomarkers such as C-reactive protein and von Willebrand factor, which consequently enhanced the progression of inflammation, endothelial dysfunction and coagulation in diabetes [26,27]. It has been indicated that overexpression of these cytokines exacerbates the severity of diabetes [4,26].…”
Section: Plasmamentioning
confidence: 97%
“…IL-1b, IL-6 and TNF-a, pro-inflammatory cytokines, were central mediators for the regulation of several biomarkers such as C-reactive protein and von Willebrand factor, which consequently enhanced the progression of inflammation, endothelial dysfunction and coagulation in diabetes [26,27]. It has been indicated that overexpression of these cytokines exacerbates the severity of diabetes [4,26].…”
Section: Plasmamentioning
confidence: 97%
“…Accordingly, we suggest that the downregulation of IL-1 b in CsA 1 allochimeric peptide treatment may be related to the immunosuppressive function of allochimeric peptide. Although it has been assumed that the source of proinflammatory cytokines in the compromised heart is infiltrating mononuclear cells, recent study on MRL/MpJ-Tnfrs6lpr (MRLlpr/lpr) mice with autoimmune syndrome showed that ventricular homogenates and ventricular cardiomyocytes constitutively over express genes encoding the proinflammatory cytokines IL-1 b, IL-6, IL-10 and gamma interferon (Tomita et al, 2004). This indicates that cardiomyocytes per se may contribute to proinflammatory cytokine production in the setting of systemic inflammation (Tomita et al, 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Although it has been assumed that the source of proinflammatory cytokines in the compromised heart is infiltrating mononuclear cells, recent study on MRL/MpJ-Tnfrs6lpr (MRLlpr/lpr) mice with autoimmune syndrome showed that ventricular homogenates and ventricular cardiomyocytes constitutively over express genes encoding the proinflammatory cytokines IL-1 b, IL-6, IL-10 and gamma interferon (Tomita et al, 2004). This indicates that cardiomyocytes per se may contribute to proinflammatory cytokine production in the setting of systemic inflammation (Tomita et al, 2004). Thus, the downregulation of the IL-1 b expression level observed in our study in CsA 1 allochimeric peptide treated animals may prevent or lower the extent of the systemic inflammation in the heart allograft.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of our present study once again supports that SEC and SMC, two compounds naturally derived from Allium plants, are potent antidiabetic agents. IL-6 and TNF-alpha, proinflammatory cytokines, were central mediators for the regulation of several biomarkers such as c-reactive protein and von Willebrand factor [18,19], which consequently contributed to the progression of inflammation, endothelial dysfunction, and coagulation. Thus, the suppression on IL-6 and TNF-alpha could retard or alleviate inflammation and improve endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%